Energy and circular transition of the industrial heritage – The Ex SNIA case in Rome - Serena Baiani; Paola Altamura; Gaia Turchetti; Giada Romano (Agathón)
The paper presents the outcomes of research activities focused on disused industrial heritage sites understood as a strategic resource for the energy and circular transition, through the adoption of regenerative actions capable of triggering new circular processes intrinsic to adaptive reuse interventions and/or activated by it and extended to the territory. The experimental approach aims to define conservation-compatible interventions within the broader framework of characterising current and potential resource flows, both material and immaterial, to achieve a circular ecosystem with zero-emission energy production, reuse and recycling of materials and water. In particular, the paper illustrates two ‘circular adaptive reuse’ scenarios on a pilot case, the most complex among the sites identified within the research activities, assessing the level of achieved circularity through specific indicators.